PENGAWASAN HANDPHONE ILEGAL OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN B PEKANBARU - Cerli Karlina; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Illegal Handphone is a term for one product that goes to the Riau Province territory not through an official (illegal) route. Because it is illegal, there is no guarantee of quality, warranty or other important factors from the manufacturer. The purpose of this study was to determine the supervision of Illegal Handphone in the City of Pekanbaru and to find out the inhibiting factors for supervision of Illegal Handphone by The Office of Customs and Excise Supervision and Service of Type Customs B Pekanbaru. The research method used is a descriptive type of qualitative research approach, the selection of informants using Purposive sampling. Techniques for collecting data through interviews, and documentation or literature. The results of this study are by The Office of Customs and Excise Supervision and Service of Type Customs B Pekanbaru not been optimal in conducting surveillance of Illegal handphone. The inhibiting factor is the lack of Human Resources from the relevant agencies, the lack of facilities and infrastructure by The Office of Customs and Excise Supervision and Service of Type Customs B Pekanbaru, and the still many rat ports in the Riau Province. It is better for a more optimal target The Office of Customs and Excise Supervision and Service of Type Customs B Pekanbaru is more assertive in overseeing illegal cellphones and goods owners supporting the Office of Customs and Excise Supervision and Service of Type Customs B Pekanbaru in monitoring so as not to so that no party is harmed, both harming the state and consumers.Keywords:Supervision, Illegal Handphone